(untitled) - Schmidt, Gary D. (New York, NY, 2023)
Seventh-grader Hercules Beal has to figure out how to fulfill his teacher's assignment of performing the Twelve Labors of Hercules in real life, and discovers important things about friendship, community, and himself along the way.
Keywords: Fiction; Brothers; Fiction; Friendship; Fiction; Fiction; Fiction; Schools; Fiction; Mythology; Middle schools; Orphans; Juvenile fiction; Mythology; Schools; Juvenile fiction; Middle schools; Juvenile fiction; Friendship; Juvenile fiction; Brothers; Juvenile fiction; Orphans; Juvenile fiction